2017
DOI: 10.1136/bmjinnov-2015-000102
|View full text |Cite
|
Sign up to set email alerts
|

Management challenges in mHealth: failures of a mobile community health worker surveillance programme in rural Nepal

Abstract: Community health workers form the backbone of healthcare systems globally. The rapid expansion of mobile communications systems represents an opportunity to improve the productivity of community health workers in rural areas. Here, we describe a programme in rural Nepal that aimed to implement a mobile phone system for collecting health surveillance data, yet did not reach its fullest potential due to several programme management challenges during the implementation of the surveillance programme. Despite early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…Similarly, a study conducted to assess the feasibility of using smartphones in maternal health care in Ethiopia reported that the health care providers who did not have previous exposure to smart phones and electronic devices were able to use the phones effectively in day-to-day maternal health care service delivery [ 48 ]. A pilot programme in rural Nepal which tested the feasibility of using mobile phones for collecting health surveillance data reported that community health workers can collect health surveillance data accurately using mobile technology if they are trained adequately [ 31 ]. There have also been studies in Nepal that demonstrated limited uptake of mental illness detection strategies among community health volunteers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study conducted to assess the feasibility of using smartphones in maternal health care in Ethiopia reported that the health care providers who did not have previous exposure to smart phones and electronic devices were able to use the phones effectively in day-to-day maternal health care service delivery [ 48 ]. A pilot programme in rural Nepal which tested the feasibility of using mobile phones for collecting health surveillance data reported that community health workers can collect health surveillance data accurately using mobile technology if they are trained adequately [ 31 ]. There have also been studies in Nepal that demonstrated limited uptake of mental illness detection strategies among community health volunteers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have assessed the feasibility and effectiveness of the application of mobile technology in health care delivery within the country. These studies have attempted to test if mobile devices can support maternal and new born child healthcare, particularly for patient data collection to send reminders for follow-up and assess signs and symptoms of illness [ 30 ]; gather health surveillance data from rural areas [ 31 ]; SMS reporting of neonatal health information and malaria surveillance [ 32 ]; support health workers in the rural district hospitals, including provision of remote specialists services [ 33 ]; aiding community health volunteers to engage persons with mental illness in treatment initiation at primary care facilities [ 34 ]; and remote supervision for mental health services [ 35 ]. None of these studies has attempted to assess the feasibility of an app-based decision aid for mental health diagnoses in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…While integrating mobile health solutions in CHWs workflow, another significant challenge faced by CHWs are management related challenges. A mobile phones system was implemented in rural Nepal to collect health surveillance data; however, it did not reach its fullest potential due to several management related challenges such as, leadership transitions, poor process design and a lack of consistent vision of how to operationalize the data [31]. The researchers concluded that for any mHealth intervention to be successful in a low-resourced settings, institutional buy-in, appropriate and actionable data collection techniques, and effective process management are essential and should be taken in to consideration [31].…”
Section: Challenges Of Using Mobile Phones For Community Health Workersmentioning
confidence: 99%
“…Prior research has shown promising use of text messages to improve uptake of health facility maternal and child health services in LMICs [ 5 , 6 ] and FCHV mobile phone use for data collection and disease surveillance following adequate training and support in Nepal [ 19 , 20 ]. Our study findings suggest that text messages could also be used to increase uptake of community health and nutrition services, such as HMGs meetings led by FCHVs, in Nepal and in similar low-resource settings.…”
Section: Discussionmentioning
confidence: 99%